Accuracy of correction of a hexapod frame, patient-specific osteotomy and reduction guides, and hinged circular external fixation in a 3D-printed canine antebrachial deformity model - Burton, Neil J.; Oxley, Bill (Frontiers in Veterinary Science, 2024)
Objectives: To objectively define whether human hexapod fixation (Maxframe), with or without the use of 3D printed positioning guides, can correct a canine antebrachial deformity with greater accuracy than the clinically established techniques of 3D patient-specific osteotomy and reduction guides (3D-PSORG) or hinged circular external skeletal fixation (CESF). Methods: CT of a canine antebrachium was manipulated to induce distal radial deformity of valgus, external torsion and procurvatum, each of magnitude 20o. Five experiments were performed to correct the deformity via a distal radial and ulna opening osteotomy using; 1) A 3D-PSORG with application of a locking plate, 2) hinged CESF, 3) Maxframe standard protocol, 4) Maxframe applied with patient-specific positioning guides (PSPG), 5) Maxframe with frame adjustment calculated from post-application CT. Following correction, all constructs were optically scanned and objective measurement of the correction achieved performed. Results: No construct returned the distal bone segment to its preoperative position in all planes. Translational malalignment in the sagittal plane was the highest magnitude of error for all constructs with the Maxframe standard protocol showing the greatest error. Maxframe (PSPG) showed the minimum error of all contracts in frontal and sagittal planes. Clinical significance: In this 3D printed model of antebrachial deformity correction, hexapod frame with the use of PSPG achieved better accuracy than 3D-PSORG and hinged CESF and may be an technique of future interest and development in the management of canine antebrachial limb deformity.